2017
DOI: 10.3390/w9020115
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Response of Climate Change in the Source Region of the Yangtze River, Based on Water Balance Analysis

Abstract: Due to the large amount of water resources stored in glaciers, permafrost, and lakes, the source region of the Yangtze River (SRYR) is of great importance for the overall basin water flow. For this purpose, a state of art review and calculations were made for the period 1957-2013 using observed hydrological and meteorological data with a water balance approach. Actual evapotranspiration was calculated and validated by empirical formulas. Water storage change analysis was conducted with uncertainty boundaries u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…The SRYR analysis of precipitation showed a significantly increasing trend (p < 0.05) in different areas depending on the season: The western part and the eastern corner in spring; western part in summer and autumn; and the central part and a small part in the southeast in winter. These results confirmed the wetting trend of the Tibetan Plateau [50] and showed the necessity to take spatial variability into account when predicting precipitation anomalies. Predictors for the models were selected considering the different spatial location.…”
Section: Discussionsupporting
confidence: 77%
“…The SRYR analysis of precipitation showed a significantly increasing trend (p < 0.05) in different areas depending on the season: The western part and the eastern corner in spring; western part in summer and autumn; and the central part and a small part in the southeast in winter. These results confirmed the wetting trend of the Tibetan Plateau [50] and showed the necessity to take spatial variability into account when predicting precipitation anomalies. Predictors for the models were selected considering the different spatial location.…”
Section: Discussionsupporting
confidence: 77%
“…Climate change and its impacts have been evident in the Qinghai Tibetan Plateau over the last decade [1][2][3][4][5]. The warming rate has been more significant during the last 50 years on the Qinghai Tibetan Plateau compared to other regions in the world with the same altitude [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Woo, et al [13] and Xu, et al [14] found that summer flows will increase due to more extreme precipitation events, more frequent warm nights, and long heatwaves in the HWYZ. Most of the studies conducted in this region were related to temperature and precipitation trends [15][16][17][18][19][20][21][22] and very few investigated linkages with stream flows [4,23,24]. The wavelet method is one of the most reliable tools for analyzing the variations in the hydrological and climatic components by the discretization of the time series into different periods and scales.…”
Section: Introductionmentioning
confidence: 99%
“…Imbalances in water supply and demand lead to shortages; specifically, global climate change, population growth, rapid urbanization, and agricultural expansion have all caused the water demands of different sectors to increase rapidly [7][8][9][10][11]. Global warming leads to increased evapotranspiration, which aggravates water cycling processes and causes increased rainfall [12][13][14][15]. However, in most arid regions where water is scarce, rainfall is decreasing, leading to an increasing imbalance between global water supply and demand [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%